Technology Optimization in 21st Century Skills Learning: Infrastructure Challenges and Strategies for Equitable Digital Access - Masnawati, Eli; Kurniawan, Yulius (Journal of Social Science Studies, 2021)
The development of technology has brought significant changes in education, especially in learning 21st century skills such as programming, creativity and collaboration. Technology offers various opportunities to improve learning effectiveness, but its application still faces a number of challenges. Infrastructure limitations, digital access gaps, and lack of educator competence to utilize technology are the main obstacles in equalizing the quality of education. This study uses a literature review approach to analyze the role of technology to support 21st century skills learning and the factors that influence the effectiveness of its implementation. The results show that although technology can increase student engagement and enrich the learning experience, without adequate support in terms of policy, funding and training for educators, the benefits cannot be optimized equally. The digital divide that occurs in various regions further widens inequalities in the quality of education. Therefore, a more comprehensive strategy is needed, including infrastructure improvement, educators training and inclusive technology-based curriculum development. Technology can function optimally to improve 21st century skills and create equitable access to education for all students. This study is expected to provide insights for education policy makers and practitioners to design more effective solutions to utilize technology in learning.